Pengaruh pendudukan Jepang terhadap penguasaan bahasa Jepang di masyarakat Ujung Pandang - Komayah, Kokom Ratna (Proyek Penelitian, Universitas Hasanuddin, 1991)
Influence of Japanese occupation on the command of Japanese language of the community in Ujung Pandang, Sulawesi Selatan Province; research report.